2017
DOI: 10.1093/nar/gkx973
|View full text |Cite
|
Sign up to set email alerts
|

ActiveDriverDB: human disease mutations and genome variation in post-translational modification sites of proteins

Abstract: Interpretation of genetic variation is needed for deciphering genotype-phenotype associations, mechanisms of inherited disease, and cancer driver mutations. Millions of single nucleotide variants (SNVs) in human genomes are known and thousands are associated with disease. An estimated 21% of disease-associated amino acid substitutions corresponding to missense SNVs are located in protein sites of post-translational modifications (PTMs), chemical modifications of amino acids that extend protein function. Active… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 70 publications
1
75
0
1
Order By: Relevance
“…Given the strong connection between PTMs, metabolism, and protein functions, several groups found that disease causing mutations or single nucleotide polymorphisms (SNPs) in patients can coincide with PTM sites (see ActiveDriver and AWESOME databases). Similarly, SNPs at PTM sites of proteins in long‐lived mammals may generate proteoforms that promote healthy aging.…”
Section: Longevity‐specific Ptm Sites?mentioning
confidence: 99%
“…Given the strong connection between PTMs, metabolism, and protein functions, several groups found that disease causing mutations or single nucleotide polymorphisms (SNPs) in patients can coincide with PTM sites (see ActiveDriver and AWESOME databases). Similarly, SNPs at PTM sites of proteins in long‐lived mammals may generate proteoforms that promote healthy aging.…”
Section: Longevity‐specific Ptm Sites?mentioning
confidence: 99%
“…Post-translational modifications (PTMs) represent a form of protein sequence variation in which the intrinsic properties of amino acids in synthesized proteins are altered via chemical modification. Recently, information derived from multiple centralized PTM resources, as well as individual studies, have been combined into a single database describing a broad range of PTM sites across the human proteome [44]. PTMs could directly affect protein aggregation by increasing or decreasing inherent aggregation propensity.…”
Section: A Survey Of Post-translational Modifications Within Human Prldsmentioning
confidence: 99%
“…The ActiveDriver database [44] is a centralized resource containing downloadable and computationally accessible information regarding "high-confidence" protein isoforms, post-translational modification sites, and disease associated mutations in human proteins. We first examined whether alternative splicing would affect predicted aggregation propensity for isoforms that map to a common gene.…”
Section: Alternative Splicing Introduces Sequence Variation That Affementioning
confidence: 99%
“…PTMs frequently correlate with the rate and severity of diseases regardless of whether they are causative or not. For instance, an analysis of disease associated amino acid substitutions revealed approximately 21% of which are located at PTM sites . Furthermore, abnormal phosphorylation of proteins is known to be a cause of cancer, diabetes, and rheumatoid arthritis .…”
Section: Introductionmentioning
confidence: 99%